Designing English Learning Website Based on Digital Literacy by Using Addie Model for English Club Extracurricular at SDN 045 Binalatung Tarakan - Laying Ayu Meriry; Arifin Arifin; Farid Helmi Setyawan (Social, Humanities, and Educational Studies (SHES): Conference Series, 2023)
This research aims to design learning media for the English Club extracurricular at SDN 045 Binalatung Tarakan using website WordPress. The research design was Research and Development (R&D) using EDDIE model. It consists of five stages (1) Analysis; (2) Design; (3) Development; (4) Implementation; and (5) Evaluation. The research instruments were questionnaires, interview, material expert validation questionnaire, media expert questionnaire (design), linguist validation questionnaire, media practicality test questionnaire, and student response questionnaire. The result of the study indicated that: 1) Expert validation obtained a total score of 34.00 which if presented as a percentage gets a score of 85% with the qualification “Eligible”; 2) Media experts obtained a total score of 57.00 with a percentage of 89.06% qualified as “Very Eligible”; 3) Linguist obtained a total score if 34.00 which if presented as a percentage, received a score of 85% with the qualification “Eligible”; and 4) Practitioner of learning English obtained a total score of 50.00 which if presented as a percentage, got a score of 83.33% with the qualification “Very Practical”. The student’s responses to this media after the trial was carried out on average showed a positive response with a percentage of 80% for each indicator. Thus, this Digital Literacy-based English Learning Website is appropriate to be used as medium for learning English in English Club extracurricular activities in Elementary Schools.